Analisis Penerapan Etika Bisnis Islam Dalam UMKM di Ayakh Ugan Pusat Oleh-Oleh Khas Baturaja - Nur Hawa; Yose Rizal Fajri (Kafalah: Jurnal Ekonomi, Manajemen, dan Keuangan Syariah, 2026)
The results of the study indicate that Ayakh Ugan has implemented most of the principles of Islamic business ethics, such as providing friendly service, maintaining honesty in transactions, and paying attention to social responsibility towards the surrounding environment. The implementation of these ethics has a positive impact on customer loyalty, business image, and business sustainability. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The theory used refers to the main principles of Islamic business ethics, namely tauhid (unity), balance (equilibrium), free will, responsibility (ihsan), and ihsan. In addition, the legal basis is taken from the Qur'an, including QS. An-Nahl verse 90, which emphasizes the importance of justice, ihsan, and the prohibition of unjust acts